Association of Maternal Short Stature to The Risk of Stunting in Low- and Middle-Income Countries: A Systematic Review of Intergenerational Nutritional Vulnerability - Sekar Putri Ramadhani; Muhammad Hidayat (International Medical Journal Corp. Ltd, 2025)
Introduction Childhood stunting, defined as low height-for-age, is a persistent global health crisis associated with delayed developmental trajectories, impaired cognitive function, and increased chronic disease risk later in life (Semba et al., 2011). Maternal short stature (MSS), typically reflecting chronic nutritional deprivation and adverse environmental exposures during the mother’s own early life, is a highly recognized predictor of offspring stunting (Wirth et al., 2019). The objective of this systematic review and meta-analysis was to rigorously quantify the pooled association between MSS and childhood stunting and to analyze the critical biological and socioeconomic effect modifiers across Low- and Middle-Income Countries (LMICs). Methods This systematic review was conducted in adherence to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA 2020) guidelines (PRISMA Statement, 2020). A comprehensive search identified 15 large observational studies, predominantly based on Demographic and Health Survey (DHS) data, focusing on children aged 0–59 months. MSS was generally defined categorically (shortest quintile or fixed cutoffs, typically <145 cm or <150 cm) compared to the tallest reference group. Study quality was assessed using the Risk Of Bias In Non-Randomized Studies – of Interventions (ROBINS-I) tool, specifically focusing on bias due to confounding (ROBINS-I; Tadesse et al., 2015). Pooled effect sizes were calculated using random-effects models and presented as Adjusted Relative Risks (RRs) or Odds Ratios (ORs). Results Analysis of 15 studies revealed a strong and highly significant association between MSS and offspring stunting (p < 0.001). The pooled categorical analysis demonstrated that children born to the shortest mothers faced an Adjusted Relative Risk (RR) of 2.85 (95% CI: 2.50, 3.25) for stunting compared to children born to the tallest mothers, indicating nearly a three-fold increased risk. Continuous analysis confirmed this protective association, showing that a 1-cm increase in maternal height significantly reduced the risk of stunting (Semba et al., 2011; Baten et al., 2019). The intergenerational effect is primarily driven by maternal physiological constraints; the mother-offspring association (RR 1.89) was substantively larger than the father-offspring association (RR 1.56), even when controlling for shared environment (Tessema et al., 2021). Discussion The observed magnitude and consistency of the association underscore the role of MSS as a potent physiological determinant of child health, reflecting an intergenerational legacy of undernutrition and poor intrauterine environment (Wirth et al., 2019). Crucially, detailed risk stratification showed that the high stunting risk associated with MSS persists relatively unchanged across socioeconomic strata, suggesting that current household affluence cannot fully mitigate the physiological constraints imposed by the mother's own historical deprivation (Baten et al., 2019). Modifiable factors such as increased Antenatal Care (ANC) visits and higher maternal education provide independent risk mitigation, offering critical intervention pathways (Tekle et al., 2021). Conclusion Maternal short stature is confirmed as one of the most significant, non-modifiable risk factors for childhood stunting in LMICs. The dominance of the maternal effect and the resistance of this risk to current socioeconomic buffering necessitate targeted, life-course interventions focusing on enhanced prenatal nutritional support and adolescent girl nutrition programs to disrupt this potent intergenerational cycle.